The Syntactic Hierarchy and Flexibility of Adverbial Placement in English - Nwogu, Aaron Ogbonnah (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2024)
This research investigates the syntactic placement of adverb phrases (AdvPs) within the clausal structure of English sentences, adapting frameworks from the study of Hindi adverbials to better understand the ordering of English adverbs. The study classifies adverbs into five primary categories based on their syntactic positions: Speech act, epistemic, and evaluative adverbs (Class I); tense-related adverbs (Class II); irrealis mood adverbs (Class III); necessity, frequency, and volitional adverbs (Class IV); and manner adverbs (Class V). By analyzing the hierarchical ordering of adverbs, this research highlights the structural framework of English sentences and examines the semantic functions of adverbs in shaping sentence meaning and tone. While the general hierarchical order is predominantly followed, the study also explores exceptions due to semantic compatibility and pragmatic factors, revealing the flexibility of adverbial placement. The findings contribute to a more comprehensive understanding of the syntactic flexibility of adverbial placement in English and provide insights into how adverbial phrases function cohesively within discourse to influence the interpretation of meaning.